Equity and pandemic preparedness: Navigating the 2024 Amendments to the International Health Regulations - Nirmalya Syam (South Centre, 2024)
The amendments to the International Health Regulations (2005) (IHR) agreed upon in May 2024 are important for strengthening global health emergency preparedness and response. The negotiations resulted in the IHR amendment now recognizing the importance of equity, including equitable access to health products, enhancing IHR core capacities, and mobilizing financing. The amendments note the role of the World Health Organization (WHO) in facilitating timely access to necessary health products by removing barriers and supporting local production and distribution. However, the WHO authority to effectively act in those areas is limited. The IHR as amended will establish a Coordinating Financial Mechanism to provide predictable and sustainable financing for its implementation, particularly in developing countries. Despite some advancements, the amendments fall short of imposing concrete obligations on developed countries to facilitate timely access to health products and financial support and transfer of technology to developing countries. Overall, the amended IHR represent a significant step toward a more equitable global health framework, setting a precedent for future international health instruments, including the proposed pandemic treaty.
Keywords: 300; Access to Health Products; Access to Medicines; COVID-19; Equity; Global Health; Health; Health Emergencies; Intellectual Property; International Health; International Health Regulations (IHR); Nirmalya Syam; Pandemic; Pandemic Preparedness and Response; Pandemic Treaty; Pandemics; Public Health; Sustainable Financing; Technology Transfer; TRIPS Agreement; World Health Organization (WHO)